Formal Requirements for Class Action Lawsuits in Environmental Cases in Indonesia: Problems and Solutions - Kurniawan, Itok Dwi; Septiningsih, Ismawati; Handayani, Fitri; Ikrimah , Afridah (Journal of Law, Environmental and Justice, 2025)
Class action lawsuits serve as a vital instrument in the enforcement of environmental law, particularly in advocating for the interests of affected communities. Although the regulation of class actions has been recognized in Indonesian legislation, such as Law Number 23 of 1997 in conjunction with Law Number 32 of 2009, as well as Supreme Court Regulation (PERMA) Number 1 of 2002, its implementation continues to face various legal and technical challenges. One of the main issues is the frequent rejection of environmental class action lawsuits by courts on the grounds of not meeting formal requirements. Therefore, the purpose of this paper is to identify procedural obstacles in the implementation of class actions and to provide policy recommendations to improve public access to environmental justice. This study employs a normative juridical method using a statutory approach. The findings indicate that PERMA Number 1 of 2002, as the legal basis for class action lawsuits, is no longer responsive to contemporary developments. To address this, two primary solutions are proposed: first, to elevate the status of PERMA to a law; and second, to establish environmental courts as a specialized forum for resolving environmental disputes. It can be concluded that a more comprehensive regulatory reconstruction and harmonization of norms within Indonesia’s civil judicial system for environmental matters is necessary to ensure the effectiveness of environmental protection through the class action mechanism.